Pengaruh Product Knowledge, Sales Promotion dan Brand Image terhadap Purchase Intention Studi Kasus: Bridestory Pay - Gharnaditya, Didiet; Saputra, Dony; Felicia, Jesslyn; Vivian, Vivian (Universitas muhammadiyah palembang, 2020)
The purpose of this study is to identify and understand the influence of Product knowledge, Sales promotion, and Brand image on the Purchase intention of the newest product from Bridestory, which is Bridestory Pay. Bridestory Pay is an electronic payment for marriage. This study uses a quantitative method by distributing questionnaires to 70 brides or grooms. Multiple linear regression is used as the method of analysis. This study uses 3 independent variables, i.e. Product knowledge, Sales promotion, and Brand image, as well as Purchase intention as the dependent variable. The result of this study are all the independent variables influence the dependent variable, Product knowledge influence Purchase intention, Sales promotion influence Purchase intention, and Brand image influence Purchase intention. With partial results Product knowledge or knowledge of the product has a significant effect on purchase intention; Sales promotion has a significant effect on purchase intention; the Brand image has a significant effect on purchase intention. Simultaneously, these variables significantly influence purchase intention. For further research can examine other variables that affect the purchase intention of Bridestory using Bridestory Pay, increase the number of respondents and add qualitative methods to explore the results of research more deeply.